Back Cover: Controlling Protein Crystal Nucleation by Droplet‐Based Microfluidics (Chem. Eur. J. 4/2014). Issue 4 (20th January 2014) - Maeki, Masatoshi; Teshima, Yuki; Yoshizuka, Saori; Yamaguchi, Hiroshi; Yamashita, Kenichi; Miyazaki, Masaya
<x xml:space="preserve">Abstract</x> Single‐protein crystals could be formed in a controlled manner by using droplet‐based microfluidics. In the Full Paper on page 1049 ff., M. Miyazaki and co‐workers show that this method was able to direct the nucleation profile of a protein by providing control over the crystallization conditions and the droplet size. The diffusion of protein molecules played an important role in the nucleation of protein crystals.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>